Gender gap–Gender-specific development in the field of obstetrics and gynecology in Germany in the last 20 years - Hertling, Stefan; Kaiser, Mario; Schleußner, Ekkehard; Loos, Franziska Maria; Eckhardt, Niklas; Graul, Isabel (Frontiers in Medicine, 2023)
Background. Gender Gap refers to differences between men and women in terms of access to medical education, career development, and leadership positions in medical practice and research. Although women now make up most medical school graduates in many countries, they are often underrepresented in higher positions. Objective. The aim of this study is therefore to analyze the gender-specific development in the field of Obstetrics and Gynecology in Germany over the past 20 years and to survey the current status quo. Materials and methods. An analysis was carried out on the development of female graduates of human medicine, the proportion of women in contract medical care and clinical care, as well as the gender-specific evaluation of obtaining a gynecological/obstetric additional qualification . habilitation figures in the field of Obstetrics and Gynecology were evaluated about gender distribution. Results. The number of physicians who have been employed in an outpatient setting has increased by 660% in the last 25 years. Epidemiologically, almost 60% of all specialists in Obstetrics and Gynecology are over 50 years old. Compared to the total number, roughly 46% (1,832/3,958) of women within gynecology are working as assistant physicians, while nearly 78% of female doctors working in hospitals are working as assistant physicians. Therefore, statistically more assistant physicians are working in other fields than in Obstetrics and Gynecology (p>0.001). At the 39 state-run university hospitals in Germany, out of the 40 chief physician positions, 10 (25%) are held by women and 30 (75%) by men. Out of the 80 leading senior physician positions to be filled, 30 are held by women (37.5%) and 50 by men (62.5%). 278 female senior physicians (61%) and 175 male senior physicians (39%) are working at German university hospitals. 656 female and male physicians are working as specialists and in specialist training (80%), and 166 male physicians are working as specialists and in specialist training (20%). Conclusion. However, it is important to recognize the need for more women in higher positions in medicine and actively work to encourage more women to choose a career in medicine.